Event-Triggered Parallel Distributed Compensator Design for Nonlinear System With Mixed Delays and Sampling Input by T-S Fuzzy Approach - Chang-Hua Lien; Hao-Chin Chang; Ker-Wei Yu; Hung-Chih Li; Cheng-Ruei Yu; Sundarapandian Vaidyanathan (IEEE Access)
In this article, the robust $H_{∞ }$ and $H_{2}$ achievement is investigated by using the proposed scheme of event-triggered parallel distributed compensator (ETPDC) for T-S delay fuzzy model with sampling input. Some nonlinear practical systems can be approximated by T-S fuzzy models. In order to implement the parallel distributed compensator of a T-S fuzzy model, the network-based computation and hardware should be designed. The resource of communication of network can be saved by the proposed ETPDC scheme developed in this article. The proposed matrix presentation approach and some inequalities are used to show and improve our developed consequences. Finally, two nonlinear practical models for mass spring damper and thermal turbine synchronous generator are illustrated to exhibit the developed main consequences.